Revisiting the roles of accounting in society - Walker, Stephen P. (Accounting, Organizations and Society, 2016)
In order to facilitate the development of new research agendas, pioneering authors in AOS embarked on difficult journeys in search of the interconnections between accounting and the social. Contributions such as Burchell et al (1980) located a number of roles of accounting in society and inspired agenda-shifting historical investigations. However, as Hopwood (1985) recognised, the participation of historians in this project requires reinvestments in theoretical and epistemological thinking. This paper encourages renewed explorations of the concepts that might guide accounting history research seeking to probe the social. Such investments are especially pressing given that notions of ‘society’ and the ‘social’ have shifted since the early years of AOS. The study charts the problems of connecting accounting and the social, indicates how social historians have addressed similar issues, and reveals the scope for drawing on other notions of the ‘social’ that have the potential to extend historical understandings of the roles of accounting in society. The latter is illustrated through a discussion of the interactions between accounting and social control.